Determinants Of Indonesian Islamic Mutual Fund Performance: The Role of Macroeconomics Variables, Dow Jones Islamic Market Index, and Mutual Fund Attributes - Rumaisha; Hilda Monoarfa; Rumaisah Azizah Al Adawiyah (Universitas Islam Negeri Alauddin Makassar, 2024)
The Islamic capital market industry has grown rapidly over the past five years; however, in 2022, Islamic capital market assets comprised only 6.42% of Indonesia's total financial assets, which are predominantly controlled by conventional finance at 89.31%. The performance of Islamic mutual funds has steadily declined over the past three years due to limited Islamic assets in the capital market, low levels of financial literacy and inclusion, and the Muslim community's preference for traditional investments such as property, gold, and bank savings. Since 2022, Islamic mutual funds have been further impacted by market volatility, high interest rates, and the revocation of tax incentives. This study uses panel data regression analysis to examine the influence of macroeconomic variables, the Dow Jones Islamic Market Index (DJIMI), and mutual fund attributes on the performance of Islamic mutual funds in Indonesia during 2019-2023. The results show that the money supply, DJIMI, and expense ratio negatively affect performance, while Indonesian crude oil prices and fund age positively impact performance, and fund size shows no significant effect. Overall, these six variables account for 96.27% of the performance of Islamic mutual funds in Indonesia. This research contributes to signaling theory, market efficiency, and provides practical insights for investors, managers, and policymakers in advancing Islamic mutual fund instruments.